Drilling fluids processing handbook (Elsevier, 2005)
Written by the Shale Shaker Committee of the American Society of Mechanical Engineers, originally of the American Association of Drilling Engineers, the authors of this book are some of the most well-respected names in the world for drilling. The first edition, Shale Shakers and Drilling Fluid Systems, was only on shale shakers, a very important piece of machinery on a drilling rig that removes drill cuttings. The original book has been much expanded to include many other aspects of drilling solids control, including chapters on drilling fluids, cut-point curves, mud cleaners, and many other pieces of equipment that were not covered in the original book. Written by a team of more than 20 of the world's foremost drilling experts, from such companies as Shell, Conoco, Amoco, and BP. There has never been a book that pulls together such a vast array of materials and depth of topic coverage in the area of drilling fluids. Covers quickly changing technology that updates the drilling engineer on all of the latest equipment, fluids, and techniques.
"ASME Shale Shaker Committee."--Cover.
Keywords: Drilling muds.; Shale shakers.; elektronické knihy; electronic books